2019
DOI: 10.26717/bjstr.2019.16.002786
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Implants: Coating with TiN

Abstract: There is a constant interaction between the orthopedic implant material and the biological environment of the living organism. The surface of this biomaterial plays a fundamental role in the implant / organism response. The surface is exposed to a corrosive environment and there may be a release of ions from the implant to the body and thus potential for adverse reactions such as inflammation and pain. It may also be subject to wear conditions, such as in joints, causing the release of wear particles to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…The higher gas flow of N 2 can increase the number of collisions between the particles. Another study [3] also reported that the formation of the Ti 2 N phase can be observed at low concentrations of nitrogen (23 at. %), whereas, at higher nitrogen concentration, the TiN phase can be expected.…”
Section: Resultsmentioning
confidence: 96%
“…The higher gas flow of N 2 can increase the number of collisions between the particles. Another study [3] also reported that the formation of the Ti 2 N phase can be observed at low concentrations of nitrogen (23 at. %), whereas, at higher nitrogen concentration, the TiN phase can be expected.…”
Section: Resultsmentioning
confidence: 96%
“…Titanium nitride (TiN) coatings were used as decorative coatings in earlier days. In the last decade, nitride coatings for orthopedic implants were also proposed to protect the implants against wear and tear and to act as a diffusion barrier layer preventing the toxic ion release from the implant metal surfaces to the human body fluids [177][178][179][180]. The physical properties of TiN coated substrates show high scratch resistance, hardness, and low frictional coefficients.…”
Section: Transition Metal Nitridesmentioning
confidence: 99%
“…For biomedical applications, TiN was found to be well tolerated by tissue due to its inertness [176]. On orthopedic implants, nitride coatings protect the surface against wear and act as a diffusion barrier, preventing ion release from the metal to the body fluids [177]. Compared to other nitrides, TiN shows better biological properties for orthopedic applications [178].…”
Section: Nitridesmentioning
confidence: 99%